Weather Information for Tribune - H. D. Bond; R. Mai (Kansas Agricultural Experiment Station Research Reports, 2016)
In 2015, annual precipitation of 21.72 in. was recorded, which is 3.82 in. above normal. Seven months had above-normal precipitation. May (6.16 in.) was the wettest month. The largest single amount of precipitation was 1.86 in. on July 20. December, the driest month, only recorded 0.08 in. of precipitation.
Keywords: Tribune Weather; 2015 weather